The Impact of Job Stress and Workload on Employee Performance: Exploring Work-Life Balance as a Mediating Factor - Rahmadanti, Windi Novita; Karya , Detri (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research investigates the influence of work stress, workload, and work-life balance on employee performance at PT. Trimitra Jaya Investama. Utilizing a quantitative descriptive approach, data were collected via questionnaires from 99 employees, and the analysis was conducted using Partial Least Square (PLS) methodology. The findings reveal that workload has a significant positive effect on employee performance, supporting existing theories that correlate manageable tasks with improved output. In contrast, work stress was found to have no significant impact on performance, either directly or indirectly through work-life balance. This suggests that employees may perceive certain levels of stress as normal, particularly among Generation Z workers, which may enhance their performance by motivating them to tackle challenges. Furthermore, work-life balance emerged as a crucial factor positively influencing performance. The study highlights the need for organizations to foster a supportive work environment that prioritizes workload management and work-life balance to optimize employee effectiveness.